2014
DOI: 10.1002/app.41020
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior of partially crosslinked poly(β‐hydroxyalkonates)/poly(butylene succinate) blends

Abstract: Partially crosslinked poly(β‐hydroxybutyrate‐co‐β‐hydroxyvalerate)/poly(butylene succinate) (PHBV/PBS) and poly(β‐hydroxybutyrate)/poly(butylene succinate) (PHB/PBS) blends were prepared by melt compounding with dicumyl peroxide. The effect of partial crosslinking on crystallization of the PHBV/PBS and PHB/PBS blends was investigated systematically. Differential scanning calorimetry results showed that the overall crystallization rates of both PHBV and PBS in their blends were enhanced considerably by the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 39 publications
0
14
0
2
Order By: Relevance
“…Despite this, its high production cost in comparison to commercial plastics, its high fragility due to high crystallinity, its relatively low melt viscosity as well as its thermal instability at moderate temperatures restrict its use [2,7]. With the aim of improving some of its properties PHB has been blended with several biodegradable polymers such as poly(lactic acid)-PLA [2,8], poly(pdioxanone)-PPD [5], poly(butylene succinate) (PBS) [9,10], poly(ethylene succinate) (PES) [11] or poly(caprolactone)-PCL [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, its high production cost in comparison to commercial plastics, its high fragility due to high crystallinity, its relatively low melt viscosity as well as its thermal instability at moderate temperatures restrict its use [2,7]. With the aim of improving some of its properties PHB has been blended with several biodegradable polymers such as poly(lactic acid)-PLA [2,8], poly(pdioxanone)-PPD [5], poly(butylene succinate) (PBS) [9,10], poly(ethylene succinate) (PES) [11] or poly(caprolactone)-PCL [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, research on biodegradable blends based on PBS and PHBV has not been extensively reported in the open scientific literature . The miscibility and crystallization behavior of PBS/PHBV blends at different compositions in the range from 80 : 20 to 20 : 80 was investigated by Qiu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, nucleation is commonly encountered at foreign surfaces, and it can thus be increased due to impurities/heterogeneities migration between the different phases during the blending process or to the presence of polymer/polymer interfaces. [1,2,10,[13][14][15][16][17]. The opposite situation, i.e., a decrease of crystallization kinetics, is also commonly observed whenever the crystallizable polymers are separated in a "sufficiently high" number of individual domains.…”
Section: Crystallization Behavior In Immiscible Blendsmentioning
confidence: 99%